The Genre of Love-Me Binders: US Military Veterans Documenting Their Service - Martell, Allan; Benoit III, Edward; Brownlee, Gillian (Archivaria)

(untitled) (Association of Canadian Archivists, 2023)
The US government lacks robust and accurate records of its military personnel. In this context, we argue that attending to veterans’ recordkeeping practices matters to honouring their service to the nation. However, recordkeeping skills are not currently part of the official curriculum of active service members or veterans. Considering this situation, we ask, How do veterans in the US document their service? What are the uses of veterans’ records and recordkeeping practices? Drawing from personal management of information (PMI) and rhetorical genre studies (RGS), we conducted focus groups with veterans and active service members. We found that these individuals attempted to preserve their personal records by creating love-me binders (LMBs) – a genre of records, shaped by the history of recordkeeping practices in the US Armed Forces, that supports military personnel in keeping track of their service. As a genre, love-me binders serve a rhetorical purpose: demonstrating that veterans and sometimes their relatives are eligible for benefits such as health care. Future work should consider opportunities to support veterans in creating and managing LMBs, investigate the creation and management of military records in context, and explore additional domains where records created in the workplace impact workers’ personal lives.